Caractérisation de la voie de l’autophagie chez l’huître creuse Crassostrea gigas en réponse à une infection par le virus OsHV-1 - Picot, Sandy (Université de La Rochelle, 2019)
Mortality outbreaks of young Pacific oysters, Crassostrea gigas, have seriously affected the aquaculture economy in several countries around the world. Although the causes for these mortalities outbreaks are complex, a viral agent was identified as the main factor, the ostreid herpesvirus 1 (OsHV-1). The mean to fight against the virus remains limited and Pacific oyster/virus interactions need to be further investigated. Recently, the results of several studies and the C. gigas genome sequencing have demonstrated the potential existence of several known mammals’ antiviral pathways in the Pacific oyster. The autophagy pathway is involved in many cellular processes including immune defense. This pathway seems to be functional in the mantle of C. gigas and involve in the response of the Pacific oyster to several pathologies including viral diseases. As part of this Phd work was to improve knowledge about the autophagy pathway mechanism in C. gigas and to decipher it modulation during the process of an infection by the virus OsHV-1. This work has highlighted a strong conservation of the pathway of autophagy at the molecular level. For the first time in C. gigas, autophagic structures were observed in haemocytes. This result has allowed to development new approaches to detect and monitor the regulation of autophagy in Pacific oyster. A monitoring of autophagy during an infection by the virus OsHV-1 showed that the viral replication is followed by a modulation of autophagy in the mantle and in haemolymph. Finally, a differential regulation of the autophagy pathway at the transcriptomic level in the mantle and haemolymph has been shown. Les importantes mortalités observées sur le naissain de l’huître creuse, Crassostrea gigas, ont fortement affecté l’économie aquacole de plusieurs pays dans le monde. Les causes de ces mortalités sont complexes, mais un agent viral appartenant à la famille des herpèsvirus, appelé ostreid herpesvirus 1 (OsHV-1), a été identifié comme étant le principal facteur responsable de ces ...